Statistik Kriminal dan Pentingnya Kebijakan Sosial Bagi Perempuan Sebagai Orang Tua Tunggal - Muhammad Ivan (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2022)
Crime statistics are still seen as data that contains numbers, crime's trends need to be improved to know the type and location of crime, furthermore it is closely related to the structural order of society and the ability to read criminal trends in the future. In this paper, the impact of criminal statistics published by the Central Bureau of Statistics which not focus on examining where the perpetrators of crime come from and what kind of family they are. Many cases of children who live with their mothers both as parents and bread winners are mostly affected by legal policies. Starting from divorce, many of these single people who raise their children experience problems with child's growth and development, this because of busy mothers as single parents need to earn a living for the family. The fatherless phenomenon (absence of a father) coupled with women as single parents further exacerbates the conditions for the development of children. Crimes originating from children who live with single mothers remains a major attention for social policy makers and law enforcers to make regulation, nevertheless Crime should not been considered normal and becomes a culture to weaknesses the social policies made by the government.